Proceedings of the 7th International Driving Symposium on Human Factors in Driver Assessment, Training, and Vehicle Design : Dr 2013
DOI: 10.17077/drivingassessment.1466
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of “Brain Training” on Changes in Driving Performance, Visual Behavior, and Neuropsychological Measures

Abstract: Summary:As the population has become both older and more technologically literate, a new class of "brain training" computer programs have gained in popularity. Though these programs have attracted substantial attention from scientists and consumers, the extent of their benefits, if any, remain unclear. Here we employ neuropsychological tests and behavioral metrics collected during periods of real-world driving (with and without manipulations of cognitive load) to evaluate the effects of training with Posit Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Additionally, it is clear that despite the continual presence of a facilitator, there was considerable variability in time spent training on individual games and, thus, in the total training received. Despite these limitations, the findings of this study are consistent with other assessments of DriveSharp’s impact on driving performance (Dobres et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, it is clear that despite the continual presence of a facilitator, there was considerable variability in time spent training on individual games and, thus, in the total training received. Despite these limitations, the findings of this study are consistent with other assessments of DriveSharp’s impact on driving performance (Dobres et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Each of the games progressed based on the improvement of the individual. The algorithms used to determine progress are not freely available, but Dobres et al (2013) have reported that the programs use a staircase to adjust the difficulty of the task, converging on a 70.7 per cent correct performance criterion. There are three exercises (see Figure 2).…”
Section: Materials and Apparatusmentioning
confidence: 99%
“…Various interventions have been developed to help older drivers to self-regulate their driving behavior and thus maintain safe driving, such as self-assessment questionnaires and self-screening tools [26][27][28][29][30][31], educational interventions associated or not with practical driving training [32][33][34][35][36][37][38][39][40][41], and cognitive training programs [42][43][44][45][46][47][48]. Self-assessment questionnaires of cognitive, physical and sensory driving-related abilities and self-screening tools of driving-related difficulties have helped older drivers to i) become aware of age-related changes that could affect their driving, ii) initiate discussion with family on driving cessation, and iii) self-regulate their driving behavior [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also investigated the benefits of cognitive training programs in terms of older drivers' driving performances. Even though cognitive training focused on speed of processing and visual attention improves these cognitive abilities relevant to driving safety [42,43,45,48], contradictory results have been reported regarding the beneficial effects of cognitive training on simulated or on-road driving performance [42-44, 46, 47]. One study showed a reduction in dangerous maneuvers on the road [42] and another showed improved braking reaction time on a driving simulator [46].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation